2017
DOI: 10.1016/j.athoracsur.2017.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Bronchus

Abstract: Communicating bronchopulmonary foregut malformations are uncommon anomalies. This report describes a case of "esophageal bronchus" managed successfully in a newborn with a nearly total pneumonectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Multiple malformations in association with this pathology, among them, esophageal atresia, stenosis or duodenal atresia, congenital heart disease, costovertebral malformations, and “pulmonary artery sling,” 14 15 are present and so the VACTERL (vertebral defects, anal atresia, cardiac defects, TEF, renal anomalies, and limb abnormalities) association should be considered, as it was ruled out in our patient. 4 11 12 16…”
Section: Discussionmentioning
confidence: 88%
“…Multiple malformations in association with this pathology, among them, esophageal atresia, stenosis or duodenal atresia, congenital heart disease, costovertebral malformations, and “pulmonary artery sling,” 14 15 are present and so the VACTERL (vertebral defects, anal atresia, cardiac defects, TEF, renal anomalies, and limb abnormalities) association should be considered, as it was ruled out in our patient. 4 11 12 16…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies showed that CBPFM can be associated with other congenital anomalies like VACTERL (vertebral defects, anal atresia, cardiac defects, tracheoesophageal fistula, renal anomalies, and limb abnormalities), pulmonary artery sling, esophageal atresia, duodenal atresia, and laryngeal cleft [ [9] , [10] , [11] ]. However, our case did not have any of these associated anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal bronchus is treated with surgical resection of the affected pulmonary lobe and reconstruction of the esophagus. 17 Esophageal lung, is usually treated with separation of the esophageal "main" bronchus, repair of the esophagus and resection of the hypoplastic lung. In both cases re-implantation of either the affected lobe or lung to the trachea is possible.…”
Section: Surgical Considerationsmentioning
confidence: 99%
“…The corresponding pulmonary lobar segment is either hypoplastic or an extralobar sequestration. The vascular supply can be systemic (aorta, inferior vena cava, azygos, or portal vein), pulmonary, or mixed 17 …”
Section: Developmental Backgroundmentioning
confidence: 99%